2010
DOI: 10.1186/1471-2334-10-356
|View full text |Cite
|
Sign up to set email alerts
|

Acute dengue virus 2 infection in Gabonese patients is associated with an early innate immune response, including strong interferon alpha production

Abstract: BackgroundDengue is now a leading cause of morbidity and mortality throughout the tropics. We conducted the first ex vivo study of dengue fever (DF) in African patients infected during the first Gabonese dengue virus 2 (DENV-2) outbreak in 2007, in order to investigate cytokine production, including the antiviral cytokine IFN-α, reported to be a potent inhibitor of DENV replication in vitro.MethodsLevels of 50 cytokines, chemokines and growth factors were measured in plasma from 36 patients with DENV-2 infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 67 publications
3
43
0
1
Order By: Relevance
“…In a study of a pediatric population with DHF, Srikiatkhachorn et al [6] also detected a rise in circulating VEGF in the early febrile and defervescent stages of Dengue infection, but not during the later convalescent stage. However, subsequent studies reported contradictory findings, as increased circulating VEGF concentrations were not observed during the early febrile and toxic stages in DHF, but lower VEGF concentrations were detected in patients with more severe Dengue infection [50][52]. Several underlying reasons may explain these differences, such as poor study design, small sample size, and the lack of a standardized collection methodology and storage of blood samples used for the measurement of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of a pediatric population with DHF, Srikiatkhachorn et al [6] also detected a rise in circulating VEGF in the early febrile and defervescent stages of Dengue infection, but not during the later convalescent stage. However, subsequent studies reported contradictory findings, as increased circulating VEGF concentrations were not observed during the early febrile and toxic stages in DHF, but lower VEGF concentrations were detected in patients with more severe Dengue infection [50][52]. Several underlying reasons may explain these differences, such as poor study design, small sample size, and the lack of a standardized collection methodology and storage of blood samples used for the measurement of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the timing of Th1 cytokine (IFN-␥, IL-10, sIL-2R, and TNF-␤) responses varies by stage of disease in humans and whether the patient presents with DF or DHF (34). A more recent study of cytokines secreted by patients with primary DENV infections in Gabon showed that TNF-␣ levels are not significantly altered but IFN-␥ levels are much higher in adults and children (7). Humanized mice infected by mosquito bite reacted in a similar manner during primary infection, with very high levels of IFN-␥ (approximately 1/10 of that seen in humans) and sIL-2R␣ (approximately 1/2 of that seen in humans) (27,28), with both cytokines produced during the viremic phase.…”
Section: Tablementioning
confidence: 99%
“…IFN-γ, TNF-α, IL-1β, IL-6, and G-CSF have previously been reported to be elevated in serum of DV-infected patients (47,48). We found that ConA treatment also elevated serum levels of these proinflammatory molecules; and we were able to recapitulate the ConA effect by treating mice with recombinant G-CSF to recruit the MDL-1 + cells, as well as a low dose of IFN-γ, TNF-α, IL-1β, and IL-6 to prime the pathogenic cells.…”
Section: Figurementioning
confidence: 99%